Peradaban islam di asia tenggara - Nafilani, Nazlia (Maliki Interdisciplinary Journal, 2025)
Islamic civilisation in Southeast Asia is a very important topic to study, given the great influence it has had on the historical and cultural development of the region. The spread of Islam to Southeast Asia began in the 7th century AD, through trade, preaching, and diplomatic relations with various kingdoms and sultanates in the region. The development of Islam in Southeast Asia was greatly influenced by various factors, such as local traditions, social systems, and interactions with outside political forces. This article aims to examine the history of Islamic civilisation in Southeast Asia, from the arrival of Islam to its impact on the social, cultural and economic structures of local communities. It also covers the contributions of Muslims in art, architecture, literature, and science in Southeast Asia. Therefore, this article will show how Islamic civilisation plays a role in the history and development of the region.